Creative strategy : A pilot evaluation of a hypothetical learning model through public speaking performance - Hafizoah, Kassim; Najah, Osman; Aziman, Abdullah (Elsevier, 2015)
To better develop thinking skills and creativity, students need to strategize their learning experiences that entail them to think and use their creative cognitive abilities. Bearing this in mind, a new learning model was developed by associating strategic thinking and creative thinking processes. We term this new model Creative Strategy Learning Model (CSLM), and we examined how the amalgam of both can provide new learning experience for learners. This study therefore measured the creative strategy learning model by employing an explorative approach, and we especially investigated its effectiveness to assist students perform better in public speaking. Researcher-developed strategic questionings and creativity checklist were used to help strategize 27 students’learning experiences in a public speaking course. Competent Speaker Speech Evaluation Form (CSSEF) was used to measure students’ public speaking performance after the implementation of the creative strategy prior to an interview session with volunteered students. Analysis of the strategic questions and creativity checklist indicated that students performed better after each phase of the learning process. The strategic questions were able to help students to cognitively strategize their learning for a better performance in the next phase, and the creativity indicator has also motivated students to perform better. Results from the CSSEF indicated excellent overall competency of public speaking. The creative strategy learning model is shown to be essential to help students develop their thinking skills and creativity for better performance in public speaking. Constant and organized feedback on their performance at each phase of the learning experience proved to positively encourage them to perform better. Nevertheless, a thorough study with increased number of participants will strengthen the findings of this pilot evaluation.